Acute mountain sickness: pathophysiology and prevention - PAWEŁ MOCZYDŁOWSKI; Karolina Kuczapska; Anna Gliwa; Monika Ryglewicz; Dariusz Fabian; Elżbieta Leszczyńska-Knaga; Natalia Jakubczyk; Weronika Rutkowska-Kawalec; Marek Kurowski; Karolina Michalczuk (Quality in Sport)
This review discusses the epidemiology, pathophysiology, prevention and treatment of acute mountain sickness (AMS). Key mechanisms including changes in blood-brain barrier permeability, activation of the renin-angiotensin-aldosterone system and the role of diuresis in the development of AMS are analysed. The effectiveness of various preventive strategies, such as acclimatisation and pharmacotherapy (acetazolamide, dexamethasone, ibuprofen), as well as alternative approaches, including the use of natural remedies such as Rhodiola roses, coca leaves and Ginkgo biloba, are discussed. The paper emphasises the importance of correct diagnosis and prompt action in the treatment of AMS, which is crucial in preventing complications.